The use of glucosamine for chronic low back pain: a systematic review of randomised control trials. Issue 6 (14th June 2013) - Sodha, Reena; Sivanadarajah, Naveethan; Alam, Mahbub
Abstract : Objectives: To ascertain whether the use of oral glucosamine influences symptoms or functional outcomes in patients with chronic low back pain (LBP) thought to be related to spinal osteoarthritis (OA). Design: Systematic review of randomised control trials. Searches were performed up to March 2011 on Medline, AMED, CINHAL, Cochrane and EMBASE with subsequent reference screening of retrieved studies. In addition, the grey literature was searched via opensigle. Included studies were required to incorporate at least one of the Cochrane Back Pain Review Group's outcome measures as part of their design. Trials with participants over 18 years with a minimum of 12 weeks of back pain, in combination with radiographic changes of OA in the spine, were included. Studies were rated for risk-of-bias and graded for quality. Results: 148 studies were identified after screening and meeting eligibility requirements, and three randomised controlled trials (n=309) were included in the quantitative synthesis. The review found that there was low quality but generally no evidence of an effect from glucosamine on function, with no change in the Roland-Morris Disability Questionnaire score in all studies. Conflicting evidence was demonstrated with pain scores with two studies showing no difference and one study with a high risk-of-bias showing both a statistically and clinically significant improvement from taking glucosamine. Conclusions: On the basis of the current research, any clinical benefit of oral glucosamine for patients with chronic LBP and radiographic changes of spinal OA can neither be demonstrated nor excluded based on insufficient data and the low quality of existing studies.